Respons Indonesia Terhadap Sengketa Laut China Selatan Semasa Pemerintahan Joko Widodo [Indonesia’s Responses toward the South China Sea Dispute During Joko Widodo’s Administration - Yuli Ari Sulistyani; Andhini Citra Pertiwi; Marina Ika Sari (Jurnal Politica, 2021)
Indonesia has been “dragged along” in the South China Sea dispute since 2010 after China claimed the Indonesian Exclusive Economic Zone in the northern region of the Natuna Islands. China’s unilateral claims continued and peaked in 2016 when Chinese fishing boats carried out illegal fishing in the Natuna waters. China’s assertive actions are intersecting with Indonesia’s national interest, prompting the Indonesian government to secure its national interest in the Natuna waters despite Indonesia being a non-claimant state in the dispute. The study aims to analyze Indonesia’s national interests in the South China Sea region and its responses amidst the dynamics of the South China Sea dispute during the reign of President Joko Widodo. A qualitative method and concepts of national interest, geopolitics, and geostrategy are applied to analyze the study. The results of the study show that Indonesia’s national interests include maintaining territorial sovereignty, sovereign rights for exploring and exploiting natural resources, as well as maintaining regional stability in the North Natuna Sea. Indonesia’s responses under Joko Widodo’s administration, in facing the South China Sea dynamics are exercised through diplomatic endeavours and military power deployments.AbstrakIndonesia mulai “terseret” dalam sengketa Laut China Selatan sejak 2010, setelah Tiongkok mengklaim Zona Ekonomi Eksklusif Indonesia di wilayah utara Kepulauan Natuna. Klaim sepihak Tiongkok terus berlanjut dan memuncak pada 2016 ketika kapal penangkap ikan asal Tiongkok melakukan aktivitas penangkapan ikan ilegal di perairan Natuna. Tindakan asertif Tiongkok tersebut bersinggungan dengan kepentingan nasional Indonesia, sehingga pemerintah Indonesia berupaya untuk mengamankan kepentingan nasionalnya di Natuna meskipun Indonesia bukan merupakan negara yang bersengketa. Studi ini bertujuan untuk menganalisis kepentingan nasional Indonesia di kawasan Laut China Selatan dan respons Indonesia di tengah dinamika Laut China Selatan pada masa pemerintahan Presiden Joko Widodo. Metode kualitatif dan konsep kepentingan nasional, geopolitik dan geostrategi digunakan untuk menganalisis studi ini. Hasil penelitian menunjukkan bahwa kepentingan nasional Indonesia di kawasan Laut China Selatan antara lain mempertahankan kedaulatan wilayah, hak berdaulat untuk mengeksplorasi dan mengeksploitasi sumber daya alam, serta menjaga stabilitas regional di Laut Natuna Utara. Di bawah pemerintahan Joko Widodo, respons Indonesia dalam menghadapi dinamika yang terjadi di Laut China Selatan dilakukan melalui upaya diplomasi dan penyiagaan kekuatan militer.